(untitled) (Research, Society and Development, 2024)
Inflammation is a biological process in response to injuries, such as infections and cellular trauma, that plays a role in eliminating invading pathogens and wound healing. Inflammation in the brain can lead to neurological disorders, highlighting the need for effective treatments. This study aimed to investigate the anti-inflammatory potential and neurological effects of Persea americana (avocado), Mangifera indica (mango), and Hancornia speciosa (mangaba). The systematic literature review revealed anti-inflammatory and neuroprotective properties of these fruits, including blood pressure reduction, improved vasodilation, and analgesic and anticonvulsant effects. The results highlight the therapeutic potential of these tropical fruits in the prevention and treatment of inflammatory and neurological conditions.